Emerging Regulatory Role of Nrf2 in Iron, Heme, and Hemoglobin Metabolism in Physiology and Disease - Kasai, Shuya; Mimura, Junsei; Ozaki, Taku; Itoh, Ken (Frontiers in Veterinary Science, 2018)
Iron has played an important role in energy production since the beginning of life, as iron-catalyzed redox reactions are required for energy production. Oxygen, a highly efficient electron acceptor with high reduction potential, facilitates highly efficient energy production in eukaryotic cells. However, the increasing atmospheric oxygen concentration produces new threats to the organism, as oxygen reacts with iron and produces reactive oxygen species unless its levels are strictly regulated. As the size of multicellular organisms increases, these organisms must transport oxygen to the peripheral tissues and begin to employ red blood cells containing hemoglobin. This system is potentially a double-edged sword, as hemoglobin autoxidation occurs at a certain speed and releases free iron into the cytoplasm. Nrf2 belongs to the CNC transcription factor family, the founding member of which is NF-E2p45. NF-E2p45 was first identified as a transcription factor that binds to the erythroid gene regulatory element NF-E2 located in the promoter region of the heme biosynthetic porphobilinogen deaminase gene. Human Nrf2 was also identified as a transcription factor that binds to the regulatory region of the -globin gene. Despite these original findings, NF-E2p45 and Nrf2 knockout mice exhibit few erythroid phenotypes. Nrf2 regulates the expression of a wide range of antioxidant and detoxification enzymes. In this review article, we describe and discuss the roles of Nrf2 in various iron-mediated bioreactions and its possible coevolution with iron and oxygen.